2000
DOI: 10.1080/j.1600-0412.2000.079001043.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is a risk factor for early pregnancy loss after IVF or ICSI

Abstract: Obesity is an independent risk factor for early pregnancy loss. This risk is, in part, related to the lower number of collected oocytes in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(70 citation statements)
references
References 24 publications
5
61
3
1
Order By: Relevance
“…Only 63% of cycles with a positive pregnancy test resulted in a live birth, and the overall early pregnancy loss rate was high (32%). The biochemical pregnancy loss rate of 16% is higher than that in routine assisted reproduction technique (11-13%) 32,33 and in our own assisted reproduction technique programme (13%). The clinical pregnancy loss rate of 13% is similar to the corresponding risk in the general population (10-15%) but less than those undergoing assisted reproduction technique (21.7 and 17.1% for singletons and twins, respectively).…”
Section: Discussioncontrasting
confidence: 50%
“…Only 63% of cycles with a positive pregnancy test resulted in a live birth, and the overall early pregnancy loss rate was high (32%). The biochemical pregnancy loss rate of 16% is higher than that in routine assisted reproduction technique (11-13%) 32,33 and in our own assisted reproduction technique programme (13%). The clinical pregnancy loss rate of 13% is similar to the corresponding risk in the general population (10-15%) but less than those undergoing assisted reproduction technique (21.7 and 17.1% for singletons and twins, respectively).…”
Section: Discussioncontrasting
confidence: 50%
“…A recent study from Finland reported that among a large group of women with oligomenorrhea and hirsutism, the most overweight women had the most profound changes in hormonal profile, that is high testosterone, high FTI and low SHBG (5). Obesity also seems to be an independent risk factor for early pregnancy loss in PCOS women (21).…”
Section: Discussionmentioning
confidence: 98%
“…28,29 Hyperinsulinemia has been implicated as an independent risk factor for early pregnancy loss. 30 Glueck et al found a very low rate of first-trimester spontaneous abortion in patients receiving metformin during pregnancy. 31 We found no difference in abortion rate.…”
Section: Discussionmentioning
confidence: 99%